Effect of zinc content on structural, functional, morphological, and thermal properties of kappa-carrageenan/NaCMC nanocomposites. (January 2021) - Sabbagh, Farzaneh; Kiarostami, Khadijeh; Khatir, Nadia Mahmoudi; Rezania, Shahabaldin; Muhamad, Ida Idayu; Hosseini, Fakhrisadat
Abstract: This study was aimed to produce a novel nanocomposite with appropriate properties to apply in biomedical researches. MgO was used as a control sample in the experiments. A series of Mg1-x Znx O nanoparticles with x = 0.01 and 0.03, were prepared by the sol-gel method and added to k-carrageenan/NaCMC to produce MgO, Mg0.99 Zn0.01 O, and Mg0.97 Zn0.03 O/k-carrageenan/NaCMC hydrogels. The structural properties were systematically investigated using X-ray diffraction (XRD), Swelling ratio %, Fourier-transform infrared spectroscopy (FTIR), Field Emission Scanning Electron Microscope (FESEM), Thermal Gravimetric Analysis (TGA), and Compression test. The FESEM analysis showed that the doping of 'Zn' in MgO had a strong effect on morphology and crystallinity of MgO nanoparticles. The MgO nanocomposite had the lowest swelling ratio. The swelling started to increase at 3.37 ± 0.95% and was found to finish at 3.81 ± 0.26%, including a peak at 22.1 ± 6.76% in the graph. The highest swelling ratio was attributed to Mg0.99 Zn0.01 O with the final ratio of 44.15 ± 1.98%. The TGA analysis revealed that total weight loss of MgOnanocomposite wasgreater than Mg0.99 Zn0.01 O, and Mg0.97 Zn0.03 O. The compression test of the nanocomposites showed that the hardness of MgO nanocomposite was the highest and it was 89.75 ± 9.19 (g), the springiness of Mg0.99 Zn0.01 O and Mg0.97 Zn0.03 O was the same and it was 10 (mm), the adhesion of Mg0.97 Zn0.03 O showed-0.848 ± 0.29 that was highest, however the consistency of Mg0.99 Zn0.01 O showed 392.90 ± 3.48 (g. sec). Highlights: The Mg0.99 Zn0.01 O and Mg0.97 Zn0.03 O nanoparticles were fabricated using sol-gel method. A novel complex of k-carrageenan/NaCMC with Mg0.99Zn0.01O nanoparticles was produced. A novel complex of k-carrageenan/NaCMC with Mg0.97Zn0.03O nanoparticles was produced. The MgO nanocomposite was produced as the control. The nanoparticles were characterized using XRD. The nanoparticles in combination with the polymers were characterized morphologically, structurally and thermally.